2020
DOI: 10.31577/caosp.2020.50.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of the alkali molecular ions in geo-cosmical plasmas

Abstract: Opacities of the solar and stellar atmospheres are caused by a large number of radiative processes. Within development of more sophisticated stellar atmosphere models, we can further investigate known processes and include all processes not considered before. We calculate the average cross-section and rate coefficients for the photodissociation of the alkali molecular ions Li + 2 , Na + 2 and LiNa + ready for further use with a particular accent to the applications for astro plasma research and low temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In Figure 2 a,b and Figure 3 a,b we present a surface plot of the averaged cross-section for photodissociation of the , , and molecular ions as a function of for a wide range of temperatures T , which are relevant for modeling laboratory [ 13 ] and astrophysical plasmas (e.g., geo-cosmic plasmas) [ 10 , 11 , 28 ]. These figures and the shape of surfaces show that exist a noticeable difference between temperature dependence of the mean thermal photoionization cross-section for different species.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 2 a,b and Figure 3 a,b we present a surface plot of the averaged cross-section for photodissociation of the , , and molecular ions as a function of for a wide range of temperatures T , which are relevant for modeling laboratory [ 13 ] and astrophysical plasmas (e.g., geo-cosmic plasmas) [ 10 , 11 , 28 ]. These figures and the shape of surfaces show that exist a noticeable difference between temperature dependence of the mean thermal photoionization cross-section for different species.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From [ 8 , 9 , 10 ] and from investigation in existing literature about the solar photospheric spectra, the absorption spectra of planetary atmospheres and the chemical composition of dust, it follows that alkali metals take part in the composition of cosmic objects [ 11 , 12 ]. It has been discovered and concluded that important characteristics of the brown dwarfs and extrasolar planets spectra might be attributed to resonance lines of alkali metal atoms broadened by collisions with ambient helium atoms and hydrogen molecules (see e.g., [ 13 , 14 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MolD contains photodissociation cross sections for individual rovibrational states of diatomic molecular ions as well as corresponding data on molecular species and molecular state characterisations calculated using a quantum mechanical method described in [110]. Since the previous VAMDC review [3], large amounts of new data concerning alkali molecular ions have been included for reference [111].…”
Section: Moldmentioning
confidence: 99%
“…As referred over the recent years the collisional processes are of great interest to the scientists (Iacob et al, 2019;Ignjatović et al, 2019;Mihajlov et al, 2012). The reason for this is that they have an effect on the spectral properties of astrophysical and laboratory plasmas (see papers Tielens, 2013;Beuc et al, 2018a,b;Srećković et al, 2014;Ignjatović et al, 2020). Collisional processes involving various species including alkali atoms, ions, and small molecule ions can have an impact on the ionization level, atom excited-state populations, and optical properties (Mihajlov et al, 2011;Srećković et al, 2017).…”
Section: Introductionmentioning
confidence: 99%